Representações sociais sobre o “Início da vida humana”: estudos comparativos entre Brasil e Espanha - Moizéis, Heloísa Bárbara Cunha (2024)
The thesis is organized into three articles. Together, these studies aim to contribute to the field of sexual and reproductive rights. The first article adopts Willem Doise's (1992) societal approach to social representations and aimed to analyze the representational contents of Brazilian and Spanish university students regarding the beginning of the human life, considering psychosocial anchorages, particularly human values and political partisanship. For this purpose, 424 university students participated, with 192 in Brazil (M=23.11; SD=6.2) and 232 in Spain (M=19.72; SD=5.7). Analyses were conducted with the assistance of the Iramuteq software, using the Descending Hierarchical Classification (DHC) procedure. The results, for both the Brazilian and Spanish samples, formed five thematic classes. Social representations for the Brazilian sample stood out for arguments exploring the possibility of the fetus being considered a potential life. In the Spanish sample, emphasis was placed on the biological aspects of human development. Regarding the second article, the aim was to verify how groups of Brazilian and Spanish students construct and organize their social representations about the social objects’ embryo and abortion. To achieve this, the structural approach proposed by Jean-Claude Abric (2003) was employed, which argues that social representations have an organized structure consisting of two systems: the central and the peripheral. In the Brazilian sample, there were 198 participants, ranging in age from 18 to 66 years (M=23.03; SD=6.14); for the Spanish group, 237 participated, ranging in age from 18 to 70 years (M=19.69; SD=5.63). The study employed hierarchical evocation tasks, and the data were processed using the Iramuteq software, through prototypical analyses. The results revealed argumentative axes where, in the Brazilian sample, the embryo is symbolically linked to life and seen as an autonomous entity, while in the Spanish sample, biological aspects of human development are highlighted. Regarding abortion, in Brazil, the practice is still associated with aspects that refer to its criminalization; for Spain, it is associated with sexual and reproductive rights. Finally, the third article, conducted only in the Brazilian context, analyzed the impact of different gestational outcomes on the level of blame attributed to a victim of sexual violence. Three studies were conducted to address this issue. The first involved 133 participants (M=25.29; SD=9.14) and investigated how the proposed conditions (abortion, full-term pregnancy, and control) affect the level of blame attributed to the victim. The second, with 161 participants (M=28.44; SD=10.01), examined how benevolent sexism predicted different levels of blame attributed to the victim through an ANCOVA (F (2, 153) = 9.89, p <.001). For participants with high adherence to benevolent sexism (BS), blame was observed on the victim in the full-term pregnancy condition compared to the abortion condition (p<0.001) and the control condition (p<0.001). The third study, with 173 students (M=27.10; SD=9.43), analyzed participants' justifications for blaming the victim for sexual violence, considering the conditions in which the victim chose to abort or carry the pregnancy to term. The societal approach of Willem Doise (1992) was adopted, utilizing BS as the psychosocial anchorage. The data were analyzed using the Iramuteq software, and a DHC analysis was performed. The results suggested the emergence of four classes, where the influence of benevolent sexism on blaming the victim in one of the classes through damage justifications was observed. Therefore, it is noted that sexist beliefs, especially benevolent ones, have a significant impact on gender roles, especially in the field of sexual and reproductive rights. This set of data presupposes that historical and cultural variations that permeate societies can influence how social representations are elaborated and socially shared, impacting favorable or unfavorable opinions regarding certain social aspects.